2012
DOI: 10.1021/jp3050725
|View full text |Cite
|
Sign up to set email alerts
|

Binding Modes of Fluorinated Benzylphosphonic Acids on the Polar ZnO Surface and Impact on Work Function

Abstract: The interfaces formed between a zinc-terminated polar zinc oxide (0002) surface and a series of chemisorbed fluorinated benzylphosphonic acids have been studied at the density functional theory level. The results indicate that there occur substantial changes in the adsorption energy and surface work function whether the binding mode is bidentate or tridentate. Also, the trends and magnitude of the various factors that determine the total modifications in work function markedly vary between the two binding mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
91
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(113 citation statements)
references
References 104 publications
20
91
2
Order By: Relevance
“…[2,23,24] In this case, the hole injection current remains constant even if the electrode WF exceeds the ionization energy of OSCs. [19,25] This is well shown in Figure 4, where the hole injection current becomes independent of the ZnO WF above 4.8 eV, which is close to P3HT ionization energy. [26] Surprisingly, hole injection from untreated ZnO (prepared in the dark) is inefficient, despite its fairly high WF of 4.7 eV.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…[2,23,24] In this case, the hole injection current remains constant even if the electrode WF exceeds the ionization energy of OSCs. [19,25] This is well shown in Figure 4, where the hole injection current becomes independent of the ZnO WF above 4.8 eV, which is close to P3HT ionization energy. [26] Surprisingly, hole injection from untreated ZnO (prepared in the dark) is inefficient, despite its fairly high WF of 4.7 eV.…”
Section: Resultssupporting
confidence: 62%
“…Herein, we found that UV light soaking decreases the WF regardless of whether the ZnO surface is additionally modified with an SAM. It has been shown that PA molecules, as used in this study undergo tridentate binding to the ZnO surface, meaning that each PA molecule occupies three surface sites. The fact that the presence of the SAM does not reduce the strength of the light‐induced WF shift suggests that this phenomenon is not entirely caused by changes of the ZnO surface chemistry, but may also involve internal surfaces such as grain boundaries .…”
Section: Resultsmentioning
confidence: 99%
“…13 After surface modification (Figure 2b−d), the two initial components (bulk oxygen and surface−OH) are markedly decreased. Furthermore, the O 1s spectrum of each SAMmodified ZnO surface can be fitted with three additional components, which were previously assigned on the basis of their binding energy shifts (with respect to the bulk oxygen) to two different PA binding modes, 13,25 i.e., bidentate and tridentate binding (red and blue components in Figure 2b−d). Table 1 summarizes the binding energies of the O 1s core levels for the three SAM-modified ZnO surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] These properties together with a type-I level alignment at the hybrid interface would be ideally suited for light-emitting applications. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The adsorption of a molecular layer on inorganic surfaces has also been exploited to tune the work function of the inorganic component. [6][7][8][9][10] Prerequisite for that is the lightinduced creation of hybrid or charge-transfer excitons, which exhibit the hole to a large extent on one side of the interface while the excited electron would reside on the other side.…”
Section: Introductionmentioning
confidence: 99%